Exploring of promising bacteria from the rhizosphere of maize, cocoa and lamtoro: Diversity, phosphate solubilizing and nitrogen fixing - Sukmawati sukmawati; AMBO ALA; BAHARUDDIN PATANDJENGI; SIKSTUS GUSLI (Society for Indonesian Biodiversity, 2020)
Abstract. Sukmawati, Ala A, Patandjengi B, Gusli S. 2020. Exploring of promising bacteria from the rhizosphere of maize, cocoa and lamtoro. Biodiversitas 21: 5665-5673. Alginate-producing bacteria are important for improving the quality of dry land, as they can both dissolve phosphate and fix nitrogen. Until now, the alginate-producing bacteria are largely isolated from seaweed. These bacteria were from the root ecosystem of cultivated plants. This study was conducted to explore bacteria that were capable of producing alginates, dissolving phosphates, and fixing nitrogen from the rhizosphere of corn (Zea mays), cocoa (Theobroma cacao), and lamtoro (Leucaena leucocephala). The characterization was carried out both morphologically and physiologically. A total of 17 isolates were successfully grown on alginate media, of which six isolates were from maize rhizosphere, five isolates from cocoa, and six isolates from the lamtoro rhizosphere. Bacterial isolates from the rhizosphere of maize and cocoa varied in terms of colony colors. In contrast, isolates from the lamtoro rhizosphere varied in colony forms. The KK1-40 isolates showed the highest cell biomass and dry weight which were 0.082 g mL-1 and 0.068 g respectively. The KK3-32 isolate showed the highest phosphate dissolution concentration of 10.85 mg L-1 with phosphate solubility efficiency value (PSE) and phosphate solubility index (PSI) which were 166.7 and a phosphate solubility index (PSI) 2.67 with a phosphate dissolution concentration of 10.85 mg L-1. LR1-25 isolates were able to fix the highest amount of nitrogen with a total N content of 0.36%. Isolates KK1-40 and LR1-25 were identified as Gram-negative bacteria and isolate KK-32 were identified as Gram-positive bacteria. The bacterial isolates KK1-40, KK3-32, and LR1-25 were superior bacteria that can be formulated to increase the productivity of dry land.